Differences in cell subsets between sun-exposed and unexposed skin: preliminary single-cell sequencing and biological analysis from a single case - Zhou, Feng; Sun, Yu; Chen, Xinling; Hou, Wenyi; Shen, Jing; Lai, Wei; Han, Kai; Zheng, Yue (Frontiers in Medicine, 2024)
The composition and subsets of skin cells continuously change in a dynamic manner. However, the specific microcosmic alterations of human photoaged skin, independent of chronologic aging, remain unclear and have been infrequently analyzed. This study aimed to evaluate biological processes and mechanisms underlying cell-subgroup alterations in skin photoaging by utilizing single cell sequencing and biological analysis from a single case. The investigation compared sun-exposed forearm skin and unexposed buttock skin from the same individual, obtained through skin punch biopsy. Our analysis identified 25 cell clusters and 12 skin cell types , revealing significant changes in unique gene expressions. A comparison of cell numbers within each cluster revealed 9 dominant cell clusters in sun-exposed skin and 16 in unexposed skin. Enrichment analysis indicated that PD-L1 expression and the PD-1 checkpoint pathway were more prominent in sun-exposed skin, while MAPK, TNF-alpha , TGF−beta and apoptosis pathways were more enriched in hair follicle cells of sun-exposed skin. This study uncovers changes in cell components in photoaged skin from a single case and provides novel insights into cellular subpopulations and pathology during the repeated UVA-induced skin damage. These findings enhance our understanding of the complex interplay between different cells in photoaged skin and offer potential targets for preventing human skin photoaging and UV-induced skin cancers.